2020
DOI: 10.1371/journal.pone.0238531
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the nitrogen accumulation in urban center river from functional genes and bacterial community

Abstract: Along with urbanization, the intensified nitrogen pollution in urban rivers and the form of black-odor rivers has become one of the biggest concerns. Better understanding of the nitrogen transformations and microbial mechanisms occurring within urban rivers could help to manage their water quality. In this study, pollution characteristics, potential nitrogen removal rate, composition and function of bacterial community, and abundance of functional genes associated with nitrogen transformation were comparativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Our study observed oxidative phosphorylation (aerobic process) and nitrogen metabolism as the dominant energy metabolism functions, followed by methane, sulphur, and carbon metabolism. The urban aquatic bodies are usually influx by a large amount of nitrogen inputs amid higher anthropogenic activities (Yu et al, 2020). The presence of nitrification genes (amoA, B, C), denitrification genes (nir, nar, nor, nos, nap), and core-forming bacterial groups such as Acetobacteraceae, Bradyrhizobiaceae , and Rhizobiaceae substantiated the higher prevalence of nitrogen metabolism in WH of urban aquatic bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study observed oxidative phosphorylation (aerobic process) and nitrogen metabolism as the dominant energy metabolism functions, followed by methane, sulphur, and carbon metabolism. The urban aquatic bodies are usually influx by a large amount of nitrogen inputs amid higher anthropogenic activities (Yu et al, 2020). The presence of nitrification genes (amoA, B, C), denitrification genes (nir, nar, nor, nos, nap), and core-forming bacterial groups such as Acetobacteraceae, Bradyrhizobiaceae , and Rhizobiaceae substantiated the higher prevalence of nitrogen metabolism in WH of urban aquatic bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Ammonium, as a major form of nitrogen in black‐odorous urban rivers, can be directly discharged or derived from nitrogen‐containing organic matter in untreated sewage. Its co‐occurrence with labile organic matter resulted in an overgrowth of both algae and heterotrophic microorganisms in black‐odorous water and easily confounded the organic matter–triggered water blackening and the N/P‐induced water eutrophication (Cao et al, 2020; Duvert et al, 2019; Liang et al, 2021; Yu et al, 2020). This study provides metadata to clarify the correlation between water blackening and eutrophication, and the two types of water pollution may be interconvertible under certain conditions based on the availability of apoptotic cell‐derived organic matter and N/P nutrients (Liang et al, 2021; Yu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Its co‐occurrence with labile organic matter resulted in an overgrowth of both algae and heterotrophic microorganisms in black‐odorous water and easily confounded the organic matter–triggered water blackening and the N/P‐induced water eutrophication (Cao et al, 2020; Duvert et al, 2019; Liang et al, 2021; Yu et al, 2020). This study provides metadata to clarify the correlation between water blackening and eutrophication, and the two types of water pollution may be interconvertible under certain conditions based on the availability of apoptotic cell‐derived organic matter and N/P nutrients (Liang et al, 2021; Yu et al, 2020). Moreover, both organic matter and N/P pollution, as environmental stresses, can destabilize microbial communities by distinctively affecting community richness and negative:positive network cohesion (Hernandez et al, 2021; Liang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%